Familial clustering, second primary cancers and causes of death in penile, vulvar and vaginal cancers - Zhang, Luyao; Hemminki, Otto; Chen, Tianhui; Zheng, Guoqiao; Försti, Asta; Sundquist, Kristina; Sundquist, Jan; Hemminki, Kari (Scientific reports, 2019)
Data on familial risks in penile and vulvar/vaginal cancers and in second primary cancers (SPCs) following these cancers are limited. We used the Swedish Family-Cancer Database from years 1958 through 2015 to identify 3641 penile and 8856 vulvar/vaginal cancers and to calculate relative risks (RRs) and 95% confidence intervals (CIs) for these cancers according to site-specific cancer in family members; additionally risk for SPCs was calculated. The familial RR for concordant (same) penile cancer was 3.22 (1.34-7.74), and it was 2.72 (1.69-4.39) for vulvar/vaginal cancer; RRs were increased for vulvar/vaginal cancer in families of anal cancer patients. RR for second penile cancer after penile cancers was 11.68 (7.95-17.18), while that for concordant vulvar/vaginal cancer was 9.03 (7.31-11.15). SPCs were diagnosed in 16.8% of penile cancer patients and in them 45.9% of deaths were caused by SPC (other than penile cancer). In vulvar/vaginal cancer patients with SPC, 36.4% of deaths were due to SPC. The results showed that these genital cancers might run in families and as SPCs are associated with human papilloma virus and smoking related cancers. Risk for these genital and anal SPCs are high and a follow-up plan should be agreed at diagnosis of these cancers.
Gesehen am 20.12.2021